Communication Management Of Baitul Muslimin Indonesia In Building A Positive Image On The Democration Party Of Indonesia Straight Against Muslimal Communications In North Summar - Hardiansyah, Tubagus Rizki; Azhar, Anang Anas; Kustiawan, Winda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study analyzed the communication management strategy of Baitul Muslimin Indonesia (Bamusi) in building a positive image of the Indonesian Democratic Party of Struggle (PDIP) among the Muslim community of North Sumatra. The study used a qualitative approach to the case study method, involving in-depth interviews of 12 key informants—consisting of Bamusi administrators, local religious figures, and Muslim communities from various Islamic organizations such as NU and Muhammadiyah as well as participatory observation and document analysis. The results show that Bamusi adopted three main strategies: a symbolic-cultural approach through religious activities, personal communication with religious figures, and dissemination of national narratives via social media. This strategy is effective especially in changing the perception of moderate Muslim groups, with 70% of informants stating that there is an improvement in PDIP image. This study emphasizes the importance of religious values-based political communication and its contribution to understanding symbolic framing and strategic communication in the context of nationalist and Islamic ideological relations.